Connections between the folk dance culture and regionality in the area of Derecske and Mikepércs - Horváth, Péter (Acta Agraria Debreceniensis, 2014)
The culture of folk dance has been prominently cultivated in Hungary nowadays, however some regions are yet to be discovered by ethnographers. Stopping this gap by this time is almost impossible due to the small number of informants. Nevertheless, memories of ethographers’ collections, motion pictures, photographs, notes and the choregraphies made from them endure, on the basis of which traditions can be reconstructed, that were so typical of some townships at one time and have been forgotten by now. What can a recreated tradition mean to a community, that sometime was left to waste by them? This is the problem the article is dealing with through the history of Derecske and Mikepércs, two townships in Hajdú-Bihar county, revealing the regional relationship system as well as late and recent potentials of the area.